Single-Center Experience With the Bare p48MW Low-Profile Flow Diverter and Its Hydrophilically Covered Version for Treatment of Bifurcation Aneurysms in Distal Segments of the Anterior and Posterior Circulation - Schob, Stefan; Kläver, Monika; Richter, Cindy; Scherlach, Cordula; Maybaum, Jens; Mucha, Simone; Schüngel, Marie-Sophie; Hoffmann, Karl Titus; Quaeschling, Ulf (Frontiers in Neurology, 2020)
Flow diversion has profoundly changed the way aneurysms are treated. However, it conventionally requires dual anti-platelet medication and has yet been considered off-label-use in the posterior circulation or within peripheral vessels of the anterior circulation. Here we report our experience with the p48MW/p48MW_HPC in the anterior and posterior circulation. This novel low-profile flow-diverter is specifically designed for treatment of small peripheral vessels and the p48MW_HPC has an anti-thrombotic-polymer-coating, which allows application of a single anti-platelet function medication in conditions that expectably require further surgery. 32 patients were prospectively included. 26 treatments were performed with one flow-diverter, four required two overlapping flow-diverters, one case demanded three overlapping flow-diverters and for one extensive dissecting aneurysm telescoping with eight flow-diverters was necessary. 22 complex bifurcation-aneurysms were treated. Three months follow up was available for 14 patients. Deployment was uneventful in all cases. In four cases under-sizing was unavoidable and resulted in significant shortening of the flow-diverter, which demanded implantation of further flow-diverters to sufficiently treat the target aneurysm. Three flow-diverters required balloon-angioplasty for optimal wall-approximation. All parent vessels remained patent. Available three month follow up studies showed decreased influx or delayed washout in all aneurysms, none was occluded completely. There were no device-related clinical complications. Implantation of the p48MW/p48MW_HPC is safe and effective for treatment of distally located cerebral aneurysms. Considering the reported rates of ischemic complications associated with flow-diversion of complex bifurcation-aneurysms, the p48MW/p48MW_HPC potentially provides increased safety for complex bifurcation aneurysms in the anterior and posterior circulation.